Interactive effect of tank-mixed post emergent herbicides and plant growth regulators on corn yield - Tkalich, Yuriy; Ткаліч, Юрій Ігорович; Tsyliuryk, Аleksandr; Цилюрик, Олександр Іванович; Masliiov, Sergey; Маслійов, Сергій Володимирович; Kozechko, Vladimir; Козечко, Володимир Іванович (Мелітопольский державний педагогічний університет ім. Богдана Хмельницького, 2018)
We proved that tank mixture (Task Extra 440 g ha-1 + Par Trend 0.2L ha-1 + Vympel 1000 g ha-1) had the maximum efficiency in corn protection against the weeds in the conditions of Northern Ukrainian Steppe. This mixture had high index of herbicide technical efficiency (96.6%) and contributed to a steady tendency to increase the plant height by 5-7 cm (2.1-2.8%), the leaf surface area by 5-6%, structure elements of the yield (cob length by 13.6 cm (5.1%), cob graininess by 18 pieces (3.9%), weight of 1000 grains by 29 g (9.1%) and grain yield by 0.33 t ha-1 (5.3%) compared to control. The tank mixture of the herbicide Titus Extra with the plant growth regulator Vympel (Titus Extra 50 g ha-1 + Par Trend 0.2L ha-1 + Pennant 500g ha-1) has also positive effect and was slightly lower than Task Extra 440 g ha-1 + Par Trend 0.2L ha-1 + Vympel 1000 g ha-1) for the grain yield by 0.12 t ha-1 (1.9%). Встановлено, що для умов північного Степу України максимальну ефективність в технології захисту посівів кукурудзи від бур’янів забезпечує бакова суміш (Таск Екстра – 440 г/га + Пар Тренд – 0,2 л/га + Вимпел − 1000 г/га), яка окрім високого показника технічної ефективності гербіциду 96,6% також сприяє стійкій тенденції до зростання висоти рослин на 5-7 см (2,1-2,8%), площі листкової поверхні на 5-6% та елементів структури урожаю (довжини качана на 13,6 см (5,1%), озерненості качана на 18 штук (3,9%), маси 1000 зерен на 29 г (9,1%) та урожаю зерна на 0,33 т/га (5,3%) порівняно з контролем без ріст регулюючих речовин. З позитивної сторони зарекомендувала себе також бакова суміш гербіциду Тітус Екстра з РРР Вимпел (Тітус Екстра – 50 г/га + Пар Тренд – 0,2 л/га + Вимпел – 500 г/га) яка дещо поступалася Таск Екстра – 440 г/га + Пар Тренд – 0,2 л/га + Вимпел − 1000 г/га, зокрема за урожаєм зерна на 0,12 т/га (1,9%).
Ефективність бакових сумішей сучасних післясходових гербіцидів та регуляторів росту рослин в посівах кукурудзи
Keywords: corn; кукурудза; weeds; бур'яни; herbicides; гербіциди; tank mixture; бакова суміш; plant growth regulator Vympel; регулятор росту рослин Вимпел; Extra Task; Екстра Таск; Titus Extra; Тітус Екстра; biometric indicators; біометричні показники